Dual‐Salt Electrolyte with Synergistic Effect for Lithium Metal Batteries with Prolonging Cyclic Performance. Issue 2 (22nd January 2022) - Jiang, Bo; Xu, Honghui; Cheng, Xiangming; Li, Jiong; Wang, Helong; Liu, Yangyang
Abstract: Along with the booming development of human society, the commercial lithium‐ion battery cannot satisfy increasing energy demand for the insufficient energy density, which is attributed to the limited theoretical capacity (372 mAh g −1 ) of graphite anode. Logically, lithium (Li) metal, which can deliver ultrahigh theoretical capacity of 3860 mAh g −1 and lowest electrochemical potential of −3.04 V versus standard hydrogen electrode, is regarded as the "holy grail" for next‐generation energy storage systems with high energy density. Nevertheless, the practical application of Li metal batteries is hampered by low Coulombic efficiency and poor cyclic performance caused by the dendritic electrodeposition. Herein, a kind of novel carbonate‐based electrolyte with a dual‐salt of hexafluorophosphate (LiPF6 ) and lithium borate difluoroxalate (LiDFOB) for stable Li anode is designed and demonstrated. The introduction of LiDFOB can not only uniform electrodeposition of Li to promote Coulombic efficiency and cycle stability, but also can suppress decomposition of LiPF6 to passivate cathode surfaces. Taking this synergistic effect, Li metal batteries with the high‐capacity ternary cathode of LiNi0.8 Co0.1 Mn0.1 O2 (NMC811) exhibits outstanding cyclic performance with high‐rate capability. Encouragingly, the posted electrolyte is expected to foster the commercial application of Li metal batteries for pursuing high‐energy density. Abstract : Dual‐salt electrolyte : The introduction of LiDFOB as the second salt in the electrolyte can not only suppress the growth of Li dendrites and thus stabilize the interphase of Li metal, but also prevents LiPF6 from decomposing to passivate the cathode surface and thus, lower the interfacial resistance. A dual‐salt electrolyte LiPF6 +LiDFOB was designed to increase the electrochemical performance of Li metal batteries that are coupled with a high‐capacity cathode of NCM811 with a wide voltage range from 3.0 V to 4.5 V.